Towards the protection of author’s moral and material interests through copyright laws: a comparative study - Alvarez Amezquita, David F. (2018)
This thesis argues that the interaction between copyright and human rights must be understood in the pitch of protecting an author’s moral and material interests. The implications of such an understanding has been analysed in three interrelated areas. One is the justification of copyright through different theories and how this can be connected to the principles of a modern conception of natural law. This has demonstrated that copyright responds to principles based on democracy, freedom of expression and equal rights of participation in the life of society. By protecting the author, society finds a mechanism that guarantees the diversity and dissemination of thoughts. Here is suggested that a concept of author should respond to the human potentiality of creativity as mean for free participation in the life of society. The second area of analysis of author’s rights is the comparative study of legislation, case law and doctrine in the mechanisms that Mexico, Argentina, Colombia, the US, the UK and Spain produce to the protection of the author. This has implied also the study of how some of those countries that have developed a constitutional structure protecting author’s interests within the understanding of the role that such a protection plays in the construction of a knowledge-based society. The study led to finding that those mechanisms related to the regulation of the contractual relationship between authors and producers are the most important for protecting author’s interests. There, the problem is to what extent the law can limit freedom of contract towards the protection of author’s interests. The international dimension of this problem shows that the narrative of protecting the author has been present in the discussion towards the construction of a universal copyright system. Such an aim of universalisation is coherent with the introduction of author’s rights in the structure of human rights, as for example in the ICESCR. The problem of regulating freedom of contract has been part of the discussions of international instruments recently in the texts of the US-Chile FTA and the TPP. It has been also considered in the recent proposal of EU Directive for Copyright in the Digital Market. However, the challenge is if a principle of protecting author's autonomy, dignity and freedom of creation which would limit freedom of contract in copyright could be reflected in an international instrument. The conclusion is that protecting the author requires attention and legal action, and that there are mechanisms at hand for such a purpose, which would add coherence to the interaction between copyright and human rights.